High-efficiency large-angle reflective composite polarization grating. Issue 2 (26th January 2020) - Zhao, Zhi-Wei; Wang, Cheng-Miao; Li, Song-Zhen; Chen, Wan; Liu, Yong-Gang; Mu, Quan-Quan; Peng, Zeng-Hui; Wang, Qi-Dong; Xuan, Li; Wei, Ru-dong
ABSTRACT: We introduce and demonstrate a new structure of polarisation grating which can substantially enlarge the deflection angle. We derive the polarisation state of a beam passing through the reflective composite polarisation grating by Jones matrix and build a rigorous simulation about the deflection angle of reflective composite polarisation grating using finite-element analysis. The theoretical diffraction efficiency of the reflective composite polarisation grating can reach up to 90%. The experimental result of deflection angle of the reflective composite polarisation grating is consistent with that of simulation. The reflective composite polarisation grating could be expected to be applied in augment reality system, spectroscopy, optical telecommunications, non-mechanical beam steering and so on. Graphical abstract: uf0001